Characteristics and attitudes of first round invitees in the Irish National Colorectal Cancer Screening Programme. Issue 5 (10th June 2020) - O'Reilly, Susanne M; Hughes, Katie N; Mooney, Therese; Fitzpatrick, Patricia; O'Donoghue, Diarmuid; McNally, Sara; Codd, Mary; Ryan, Elizabeth; Doherty, Glen; Mason, Olivia; Mulcahy, Hugh E; Cullen, Garret
Abstract : Background/objective: Colorectal cancer (CRC) screening is proven to reduce CRC-related mortality. Faecal immunochemical testing (FIT)-positive clients in the Irish National CRC Screening Programme underwent colonoscopy. Round 1 uptake was 40.2%. We sought to identify barriers to participation by assessing knowledge of CRC screening and examining attitudes towards FIT test and colonoscopy. Methods: Questionnaires based on a modified Champion's Health Belief Model were mailed to 3500 invitees: 1000 FIT-positive, 1000 FIT-negative and 1500 non-participants. 44% responded: 550 (46%) FIT-positive, 577 (48%) FIT-negative and 69 (6%) non-responders (NR). Results: 25% of respondents (n=286) did not perceive a personal risk of cancer, did not perceive CRC to be a serious disease and did not perceive benefits to screening. These opinions were more likely to be expressed by men (p=0.035). One-fifth (n=251) found screening stressful. Fear of cancer diagnosis and test results were associated with stress. FIT-positive clients, women and those with social medical insurance were more likely to experience stress. Conclusions: The CRC screening process causes stress to one-fifth of participants. Greater use of media and involvement of healthcare professionals in disseminating information on the benefits of screening may lead to higher uptake in round 2.